1979
DOI: 10.1083/jcb.82.1.57
|View full text |Cite
|
Sign up to set email alerts
|

N-ethylmaleimide-modified heavy meromyosin. A probe for actomyosin interactions.

Abstract: Treatment of rabbit skeletal muscle heavy meromyosin (HMM) with the sulfhydryl reagent N-ethylmaleimide (NEM) produces a species of HMM which remains tightly bound to actin in the presence of MgATP. NEM-HMM forms characteristic "arrowhead" complexes with actin which persist despite rinses with MgATP. NEM-HMM inhibits the actin activation of native HMM-ATPase activity, the superprecipitation of actomyosin, the contraction of glycerinated muscle myofibrils, and the contraction of cytoplasmic strands of the soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…The reaction was stopped by adding DTT to a final concentration of 10 mM, and unreacted NEM was removed by exhaustive dialysis. ATPase activities of the treated proteins were measured as described previously (24). As with NEM-HMM, the calcium ATPase activity of NEM-S, was elevated above that of S,, and the actin-activated and K*/EDTAstimulated ATPase activity of NEM-S, was < 10% that of the untreated proteins.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction was stopped by adding DTT to a final concentration of 10 mM, and unreacted NEM was removed by exhaustive dialysis. ATPase activities of the treated proteins were measured as described previously (24). As with NEM-HMM, the calcium ATPase activity of NEM-S, was elevated above that of S,, and the actin-activated and K*/EDTAstimulated ATPase activity of NEM-S, was < 10% that of the untreated proteins.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that NEM-HMM forms rigorlike bonds even in the presence of ATP and blocks actomyosin interactions in several model systems by preventing unmodified myosin from interacting with the actin microfilament (24). NEM-S, probably inhibits cleavage by a similar mechanism, that is, it may prevent native myosin from interacting with filaments in the contractile ring.…”
Section: Cleavage Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…26. Beads, sparsely covered with motor protein, were positioned over tetramethylrhodaminephalloidin-labeled and aligned actin filaments attached to a coverslip by myosin-II treated with N-ethylmaleimide (26,47). Before each experiment the trap stiffness was calibrated for the trapped bead from the amplitude of the thermal diffusion (48).…”
Section: Methodsmentioning
confidence: 99%